Kindgerechte Websites als Kundenbindungsinstrument für Unternehmen: Eine Analyse der Internet-Angebote von Aldi Süd und Mattel / Barbie in Bezug auf die Kundenloyalität - Annika S. Zelinsky; Florian Botzenhardt; Hans-Michael Ferdinand (Markenbrand, 2016)
– Children play a key role when it comes to their parents' buying decisions. It is obvious that this is an important fact for brands and their products. For strong brand-consumer-relationships it is very interesting to start building this relationship as early as possible and ethically acceptable. Looking at children, the internet has become a very important channel for information and entertainment. From a marketing perspective it feels natural to offer tailor-made websites for a young audience. This article examines if specific websites for children have a positive impact on customer loyalty. Out of literature review, 10 criteria for establishing a child-brand-relationship are defined. Based on this list of criteria, two german websites are analyzed: ALDIlino, the children-oriented website by the discount market-leader ALDI and the website of Barbie, the well-known Brand by Mattel. The analysis shows that child-oriented websites can have a positive effect on customer loyalty if the websites are built with the specific requirements of children in mind.
Keywords: 650